2004
DOI: 10.1007/s00464-003-9269-4
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery (VATS) segmentectomy for small peripheral lung cancer tumors: intermediate results

Abstract: The present results are intermediate only; the rate of long-term survival and the advantages of the less invasive procedure still need further investigation. Nevertheless, we believe that VATS segmentectomy with complete lymph node dissection is a reasonable treatment option for selected patients with small peripheral NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 22 publications
0
37
1
3
Order By: Relevance
“…VATS is less invasive and provides benefits due to the rapid postoperative recovery and shortening the hospital stay. 4) We have reported that VATS segmentectomy for early stage lung cancer is a good surgical option when the patient is well-selected 5,6) ; however, VATS sublobar resection as definitive management for early stage lung cancer remains controversial and might be associated with increased local recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
“…VATS is less invasive and provides benefits due to the rapid postoperative recovery and shortening the hospital stay. 4) We have reported that VATS segmentectomy for early stage lung cancer is a good surgical option when the patient is well-selected 5,6) ; however, VATS sublobar resection as definitive management for early stage lung cancer remains controversial and might be associated with increased local recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
“…Our surgical technique is similar to a previous report 8) ; if necessary, a utility access port of 3-4 cm in length was added to the 4 ports. All procedures were performed by visualization through a monitor, so-called complete VATS or total thoracoscopy.…”
Section: Surgical Techniquementioning
confidence: 84%
“…Based on our previous experience with the uniportal VATS technique, we started to perform the subxiphoid approach for lobectomy with the potential advantage of decreased postoperative pain, better cosmesis and easier specimen retrieval compared to the transthoracic approach (13). Segmental anatomic resections are more complex procedures and require a perfect knowledge of the distal lung anatomy (14). The increased use of low-dose CT for screening will result in more diagnosed lung cancer in the early stage (15) therefore segmentectomy is being performing more frequently.…”
Section: Discussionmentioning
confidence: 99%